Coexistence of restless legs syndrome and multiple sclerosis aggravates anxiety and depression - Serhan SEVIM; Meltem DEMIRKIRAN; Murat TERZI; Nur YÜCEYAR; Bahar TAŞDELEN; Egemen İDIMAN; Murat KÜRTÜNCÜ; Cavit BOZ; Deniz TUNCEL; Rana KARABUDAK; Aksel SIVA; Abdülcemal ÖZCAN; et al. (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Among the comorbidities that accompany multiple sclerosis (MS), restless legs syndrome (RLS) is one of the most common. Anxiety and depression are common psychological comorbidities that impact the quality of life of patients with MS (PwMS), as well as patients with RLS. Objective: To investigate the psychiatric burden of MS and RLS coexistence, we conducted a nationwide, multicenter and cross-sectional survey. Methods: Participants were assessed by using demographic and clinical parameters along with the Hamilton Anxiety and Hamilton Depression Scales (HAM-A and HAM-D). Results: Out of the 1,068 participants, 173 (16.2%) were found to have RLS [RLS(+)] and 895 (83.8%) did not [RLS(-)]. The mean scores for HAM-A and HAM-D were significantly higher among RLS(+) subjects than among RLS(-) subjects (p<0.001 for all variables). Conclusions: According to our data, the presence of RLS in PwMS may increase the occurrence of both anxiety and depression symptoms. Awareness and treatment of RLS in PwMS could possibly reduce the symptoms of psychiatric comorbidities originating from RLS.